TRANSVERSAL TETRA-HEMIMELIA WITH MULTIPLE CRANIOFACIAL ANOMALIES IN A BUFFALO CALF - HONPARKHE, M; LOCHAN, S; SHIVKUMAR, SHIVKUMAR; KUMAR, N; KUMAR, A (The Indian Journal of Animal Reproduction, 2016)
This report depicts about a rare case of transversal tetra-hemimelic buffalo calf with multiple craniofacial defects and its successful vaginal delivery through fetotomy